The Role of the Internal Quality Assurance Unit in Study Program Accreditation at State Islamic Higher Education Institutions - Haryanto, Endang; Makmur; Nur Hariyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Quality assurance is a fundamental element in the implementation of higher education in higher education institution in Indonesia is required to implement an Internal Quality Assurance System (SPMI) as a mechanism for continuous quality control and improvement. SPMI plays a crucial role in supporting the study program accreditation process conducted by external quality assurance agencies. This study aims to analyze the implementation of the Internal Quality Assurance System (IQAS) at the English Education Study Program of the State Islamic Institute (IAIN) Curup in achieving excellent accreditation status. This research employed a qualitative approach using a case study design. Data were collected through in-depth interviews, observation, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the implementation of IQAS in the English Education Study Program has been systematically carried out through the PPEPP cycle, consisting of Determination, Implementation, Evaluation, Control, and Improvement. This system is strengthened by the role of the Quality Assurance Group, Internal Quality Audit, and the integration of Outcome-Based Education (OBE) in curriculum development and learning processes. A strong quality culture within the study program serves as a key factor in achieving “Excellent” accreditation. Based on this study the data indicated that English study program of IAIN Curup empowering the roles of SPMI Involved